Microneedle-assisted topical delivery of photodynamically active mesoporous formulation for combination therapy of deep-seated melanoma - Tham, Phoebe Huijun (2021)
Topical treatment using photodynamic therapy (PDT) for many types of skin cancers has largely been limited by the inability of existing photosensitizers to penetrate into the deep skin tissue. To overcome these problems, we developed a mesoporous nanovehicle with dual loading of photosensitizers and clinically relevant drugs for combination therapy, while utilizing microneedle technology to facilitate their penetration into deep skin tissue. Sub-50 nm photodynamically active mesoporous organosilica nanoparticles were synthesized with photosensitizers covalently bonded to the silica matrix, which dramatically increased the quantum yield and photostability of these photosensitizers. The mesopores of the nanoparticles were further loaded with small-molecule inhibitors, i. e., dabrafenib and trametinib, that target the hyperactive mitogen-activated protein kinase (MAPK) pathway for melanoma treatment. As-prepared empty nanovehicle was cytocompatible with normal skin cells in the dark, while NIR-irradiated drug-loaded nanovehicle showed a synergistic killing effect on skin cancer cells mainly through reactive oxygen species and caspase-activated apoptosis. The nanovehicle could significantly inhibit the proliferation of tumor cells in a 3D spheroid model in vitro. Porcine skin fluorescence imaging demonstrated that microneedles could facilitate the penetration of nanovehicle across the epidermis layer of skin to reach deep-seated melanoma sites. Tumor regression studies in a xenografted melanoma mouse model confirmed superior therapeutic efficacy of the nanovehicle through combinational PDT and targeted therapy.